Somatic expression of piRNA and associated machinery in the mouse identifies short, tissue-specific piRNA. Issue 5 (4th May 2019) - Perera, Bambarendage P.U.; Tsai, Zing Tsung-Yeh; Colwell, Mathia L.; Jones, Tamara R.; Goodrich, Jaclyn M.; Wang, Kai; Sartor, Maureen A.; Faulk, Christopher; Dolinoy, Dana C.
ABSTRACT: Piwi-interacting RNAs (piRNAs) are small non-coding RNAs that associate with PIWI proteins for transposon silencing via DNA methylation and are highly expressed and extensively studied in the germline. Mature germline piRNAs typically consist of 24–32 nucleotides, with a strong preference for a 5ʹ uridine signature, an adenosine signature at position 10, and a 2ʹ-O-methylation signature at the 3ʹ end. piRNA presence in somatic tissues, however, is not well characterized and requires further systematic evaluation. In the current study, we identified piRNAs and associated machinery from mouse somatic tissues representing the three germ layers. piRNA specificity was improved by combining small RNA size selection, sodium periodate treatment enrichment for piRNA over other small RNA, and small RNA next-generation sequencing. We identify PIWIL1, PIWIL2, and PIWIL4 expression in brain, liver, kidney, and heart. Of note, somatic piRNAs are shorter in length and tissue-specific, with increased occurrence of unique piRNAs in hippocampus and liver, compared to the germline. Hippocampus contains 5, 494 piRNA-like peaks, the highest expression among all tested somatic tissues, followed by cortex (1, 963), kidney (580), and liver (406). The study identifies 26 piRNA sequence species and 40 piRNA locations exclusive to all examined somatic tissues. Although piRNA expression has long been considered exclusive to the germline, our results support that piRNAs are expressed in several somatic tissues that may influence piRNA functions in the soma. Once confirmed, the PIWI/piRNA system may serve as a potential tool for future research in epigenome editing to improve human health by manipulating DNA methylation.